PENENTUAN GARIS BATAS WILAYAH ANTARA INDIA DAN CINA DI WILAYAH AKSAI CHIN BERDASARKAN HUKUM INTERNASIONAL: Determination of Territorial Boundaries between India and China in the Aksai Chin Region Based on International Law - Ramadhan, Andi Muhammad Fauzi; Lutfah, Diny (Faculty of Law, Universitas Trisakti, 2024)
India and China have experienced problems in determining the boundaries of the Aksai Chin region from 1962 to the present. Various efforts made since the 1990s until now have not resulted in an agreement on dispute resolution and also the determination of legal boundaries between the two countries. The issues raised are how to determine the boundaries of the territory according to international law and how the efforts between India and China in determining the boundaries of the Aksai Chin area based on international law. This type of research uses normative research, is descriptive in nature, secondary data and primary data are analyzed qualitatively and the method of drawing conclusions uses deductive logic. Based on the results of the study that: there are many efforts that can be made by India and China in determining the boundaries of areas that have been regulated by international law. Therefore, India and China can use amicable and peaceful means and enter into a Mutual agreement